The Relationship Between Mindfulness, Depressive Symptoms, and Non-Suicidal Self-Injury Amongst Adolescents. Issue 4 (1st October 2016) - Heath, Nancy L.; Carsley, Dana; De Riggi, Melissa E.; Mills, Devin; Mettler, Jessica
Abstract : Mindfulness is often part of treatment for non-suicidal self-injury (NSSI); however, there has been limited research examining the role of mindfulness in NSSI. Thus, the current study sought to investigate the relationship among mindfulness, depressive symptoms, and NSSI (past year) in adolescents (N = 764; 56.8% female, M age = 14.42, SD = 0.64) with consideration of gender. Adolescents with recent NSSI (n = 74; 83.8% female, M age = 14.36, SD = 0.56) and a matched for age and gender no-NSSI group completed measures of mindfulness and depression. Findings revealed that mindfulness and depressive symptoms were negatively correlated, although significantly less so for the NSSI group. Second, the NSSI group reported greater depressive symptoms and less mindfulness. Finally, mindfulness was found to partially mediate the effect of depressive symptoms on NSSI. The present study is the first to provide empirical support for the protective role of mindfulness in NSSI.